(x+5)(x+12)=18

Simple and best practice solution for (x+5)(x+12)=18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+5)(x+12)=18 equation:



(x+5)(x+12)=18
We move all terms to the left:
(x+5)(x+12)-(18)=0
We multiply parentheses ..
(+x^2+12x+5x+60)-18=0
We get rid of parentheses
x^2+12x+5x+60-18=0
We add all the numbers together, and all the variables
x^2+17x+42=0
a = 1; b = 17; c = +42;
Δ = b2-4ac
Δ = 172-4·1·42
Δ = 121
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{121}=11$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(17)-11}{2*1}=\frac{-28}{2} =-14 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(17)+11}{2*1}=\frac{-6}{2} =-3 $

See similar equations:

| x/9-14=22 | | -8d=-8-9d | | 6n-32=4(1-3n) | | 5(y-4)=7(2y-1 | | 8x–20=5x+4 | | x÷9-14=22 | | 3(x-3)-5=19 | | 13x-2=12x+7+2 | | 8x+2=-18+x | | -5(1+4m)=-8+4m | | 2x+3(5=2x)+3 | | -12x+10=42x-10 | | -5x+5=4x-13 | | x+x+2+3x-6=31x+x+2+3x−6=31 | | 65+10x=35-5x | | -3x18=7x | | 17x=8=22x-7 | | 6(2-v)-v=2(v+1) | | 2)22=1+8a+5 | | 2(3n+1.5)=5(n–4)​ | | 15-9(2x+3)=-16x+40 | | 3(x-2)=2x-4+x-1 | | 10y+19.95=139.96 | | 2^x+2+2^x+1=9 | | X/3+6=x/9-10 | | 12x+10=5-6x | | -25-10r=5(-6+2r) | | 4x2-12=4x2+2x-7 | | 84=-12+b | | 12x+14-3x+7=7(x+3)+2x | | 6x²+15x+135=0 | | -7+4(c+8)=-2(c-1) |

Equations solver categories